The Statue of a Doctor Who Experimented on Enslaved Women still Stands in Alabama. But now There’s also a Monument to His Victims. - Matchan, Linda (Washington Post, 2021)
Michelle Browder’s “The Mothers of Gynecology” remembers Black women who endured surgeries without anesthesia, or consent.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice noir.e; _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Performing Resistance/Negotiating Sovereignty: Indigenous Women's Perofrmance Art in Canada - Taunton, Carla Jane (Queen's University, 2011)
Performing Resistance/ Negotiating Sovereignty: Indigenous Women’s Performance Art In Canada investigates the contemporary production of Indigenous performance and video art in Canada in terms of cultural continuance, survivance and resistance. Drawing on critical Indigenous methodology, which foregrounds the necessity of privileging multiple Indigenous systems of knowledge, it explores these themes through the lenses of storytelling, decolonization, activism, and agency. With specific reference to performances by Rebecca Belmore, Lori Blondeau, Cheryl L'Hirondelle, Skeena Reece and Dana Claxton, as well as others, it argues that Indigenous performance art should be understood in terms of i) its enduring relationship to activism and resistance ii) its ongoing use as a tool for interventions in colonially entrenched spaces, and iii) its longstanding role in maintaining self-determination and cultural sovereignty.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Embodying Sovereignty: Indigenous Women’s Performance Art in Canada - Taunton, Carla (Narratives Unfolding: National Art Histories in an Unfinished World, 2017)
Homi Bhabha’s pivotal 1994 book,The Location of Culture, begins with an epigraph from Heidegger’s “Building Dwelling Thinking”: “A boundary is not that at which something stops but, as the Greeks recognized, the boundary is that from whichsomething begins its presencing.” Cultural engagement, whether antagonistic or affiliative in nature, is produced performatively – not as a reflection of something that is given or set in stone, but as an ongoing process of negotiation.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Re-Inventing Art Practices: Indigenous Women Artists Building Community through Art and Activism in Rural and Remote Manitoba - Nagam, Julie (University of Manitoba, 2006)
his thesis documents and explores community-based and socially engaged art by Indigenous women artists. Their artwork is impacting and strengthening communities in Manitoba. The Thesis explores the use of dialogical aesthetics in performance and socially-engaged art by Indigenous women artists in rural and remote areas of Manitoba, and relates these aesthetics to the concept of activism through their art and relationship to their community. The aim of this research and this paper is to document, support and expose the work of a small pocket of Indigenous women artists in Manitoba who are acting as activists or social change agents based on their artwork. I have arrived at this conclusion first by their personal testimonies, second, by their art being socially conscious and lastly, by their art practices entrenched in the framework of dialogical aesthetics, community-based and site-specific ideologies.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

(Re)Mapping the Colonized Body: The Creative Interventions of Rebecca Belmore in the Cityscape. - Nagam, Julie (American Indian Culture and Research Journal, 2011)
The cityscape holds the memories of indigenous bones and bodies that resurrect a deep sense of place that exists in the landscape of the city of Toronto. This deep sense of place is part of a connection to the land and stories of place. In this article, the author bridges the creative work of Anishinaabe artist Rebecca Belmore with the living histories of the indigenous bodies and bones that are buried beneath the ground of the city of Toronto and the city of Vancouver. She argues that Belmore's artwork is part of the living archive that performs cultural memory and employs telling as part of an embodied experience and a political act. Belmore's performance work creates, records, and stores indigenous stories of place. This article uses the ideas of cultural theorists Katherine McKittrick, Mishuana Goeman, and Matthew Sparke. Each of these people brings a different element to theories of the body and space. This article also uses feminist geographers Alison Blunt and Gillian Rose's work in women's colonial geographies to unpack the affects of the map in colonial spaces and the colonial gaze. (Contains 4 figures and 50 notes.)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Becoming our future: global indigenous curatorial practice - Nagam, Julie; Tamati-Quennell, Megan; Lane, Carly (ARP Books, 2020)
"This book investigates international Indigenous methodologies in art curatorial practice from the geographic spaces of Canada, Aotearoa (New Zealand) and Australia. From a perspective of Indigenous peoples important place within society, this collection explores how Indigenous art and culture operate within and from a structural framework that is unique and is positioned outside of the non-Indigenous cultural milieu. Through a selection of contributions, Becoming Our Future articulates this perspective, defines Indigenous curatorial practice and celebrates Indigenous sovereignty within the three countries. It begins to explore the connections and historical moments that draw Indigenous curatorial practices together and the differences that set them apart. This knowledge is grounded in continuous international exchanges and draws on the breadth of work within the field. With contributions by Nigel Borell, Nici Cumpston, Freja Carmicheal, Karl Chitham, Franchesca Cubillo, Léuli Eshraghi, Reuben Friend, Jarita Greyeyes, Heather Igloliorte, Jaimie Isaac, Carly Lane, Michelle LaVallee, Cathy Mattes, Bruce McLean, Kimberley Moulton, Lisa Myers, Julie Nagam, Wanda Nanibush, Jolene Rickard, Megan Tamati-Quennell, and Daina Warren."-- Provided by publisher.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Dans toute son exubérance : Affirmation de soi et autoreprésentation chez Caroline Monnet - Marcoux, Gabrielle (Canadian Journal of Film Studies, 2020)
In this interview, multidisciplinary artist Caroline Monnet discusses how acts of critical self-representation open up new spaces for territorial, linguistic, and identity negotiations and affirmations for Indigenous creators. In this sense, Monnet expresses her desire to put forward exuberant, strong, and diverse representations of Indigenous women in order to counter pervasive rhetorical dynamics of victimhood conveyed by mass media and cinema. As she presents some of the visual and discursive techniques she develops through her films, installations, and photographic works, Monnet reflects on the constructive dialogues – as well as the moments of incommunicability – that emerge and fade within various spaces and contexts of creation and reception. She considers that her individual and collective creative projects fall within a pivotal period of self-determination for Indigenous artists; she thus provides a critical overview of current discourses of (re)concililation.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L’œuvre documentaire d’Alanis Obomsawin et la voix des femmes autochtones. - Bertrand, Karine (De l'exclusion à la solidarité: regards intersectionnels sur les médias, 2020)
Résumé livre : "L’intersectionnalité, telle qu’élaborée par les féministes noires dans les années 1980, permet de réfléchir aux rapports de pouvoir dans leur complexe enchevêtrement. Au-delà d’un certain effet de mode, cette éthique est plus que jamais nécessaire pour comprendre le monde, à l’aube d’une décennie marquée par un virus ayant partout exacerbé la violence et les inégalités, et mis en évidence les systèmes de privilèges. Et qu’arrive-t-il lorsque l’on porte ce regard attentif sur les médias ? Les textes rassemblés dans cet ouvrage explorent avec aplomb les questions de l’inclusion et de l’exclusion médiatiques. Que décoder du traitement média réservé au port du hijab dans le sport, aux agressions sexuelles à l’endroit des femmes noires et autochtones, ou encore, de la place de la sourditude et des transidentités dans l’espace public? Un recueil qui amène son lot de réponses éclairantes et douloureuses, une rareté dans le paysage des études culturelles et médiatiques francophones."--Page 4 de la couverture
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Remembering Vancouver's Disappeared Women: Settler Colonialism and the Difficulty of Inheritance - Dean, Amber (University of Toronto Press, 2015)
"Between the late 1970s and the early 2000s, at least sixty-five women, many of them members of Indigenous communities, were found murdered or reported missing from Vancouver's Downtown Eastside. In a work driven by the urgency of this ongoing crisis, which extends across the country, Amber Dean offers a timely, critical analysis of the public representations, memorials, and activist strategies that brought the story of Vancouver's disappeared women to the attention of a wider public. Remembering Vancouver's Disappeared Women traces "what lives on" from the violent loss of so many women from the same neighborhood. Dean interrogates representations that aim to humanize the murdered or missing women, asking how these might inadvertently feed into the presumed dehumanization of sex work, Indigeneity, and living in the Downtown Eastside of Vancouver. Taking inspiration from Indigenous women's research, activism, and art, she challenges readers to reckon with our collective implication in the ongoing violence of settler colonialism and to accept responsibility for addressing its countless injustices
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Auto-histoires et représentations communautaires dans le cinéma des femmes autochtones - Bertrand, Karine (Canadian Journal of Film Studies, 2020)
In the last decade or so, cinema has revealed itself to be an ideal medium for the transfer and/or remediation of the spoken word as well as stories coming from oral tradition and Indigenous culture. Indeed, cinema is a place of expression which favours cyclical creativity and contributes to the decolonization of stereotyped images propagated by external voices that do not understand the subtleties of languages (real and symbolic) that are anchored in indigenous peoples’ cultural memory. By exploring indigenous cinema as practised by women of diverse nations, this piece demonstrates how cinema can induce the compression and dilation of time, to bring to the audience the fluidity of a story that has been reconfigured according to a new time and carried by spoken words that have chosen to either emancipate themselves from the image or to materialize themselves in it. Furthermore, this article illustrates how a new generation of Indigenous women use cinema to retrace and/or rewrite their personal narrative with the help of autobiographical or collective stories that travel back in time to fill in the blanks left by a fragile memory and to express their will to make peace with a difficult colonial past. Finally, the writings of Lee Maracle (I Am Woman, 1988) and Natasha Kanapé Fontaine (Manifeste Assi, 2014) are being brought forth to show how films such as Suckerfish (Lisa Jackson, 2004) Bithos (Elle-Máijá Tailfeathers, 2015) and Four Faces of the Moon (Amanda Strong, 2016) contribute to the individual and community healing of Indigenous peoples of Canada, through an aesthetic of reconciliation. The exploration of these works, therefore allows us to shed light on and better understand the roles/internal mechanisms of visual autobiographies in the larger context of reconciliation with individual and collective stories/memories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Sovereignty and Settler Amnesia: Robert Houle's "Premises for Self Rule" - Ernst, Stacy A. (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Le modernisme en art est souvent considéré comme un développement spécifiquement occidental. Robert Houle, l'artiste, écrivain et commissaire d'exposition d'origine Saulteaux, a cependant toujours soutenu que sa propre pratique est moderniste et qu'elle suit une filiation esthétique autochtone. Cet article s'intéresse particulièrement à une œuvre produite par Houle en 1994, Premises for Self Rule, dans laquelle l'artiste a juxtaposé des textes de législation coloniale à des panneaux peints en monochrome et des cartes postales trouvées en archives. Il propose qu'à travers cette stratégie de rapprochement, l'artiste fusionne la tradition de la peinture de parflèche à l'esthétique moderniste, remettant ainsi en lumière la négociation interculturelle, l'amnésie coloniale, ainsi que les écarts qui séparent les épistémologies et traditions artistiques des peuples autochtones et allochtones
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

The Art of Community - de Stecher, Annette (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
La nation huronne-wendat de Wendake (Lorette, Québec) a maintenu sa culture et son identité pendant des siècles, souvent en dépit de, et en résistance contre les pressions occasionnées par la présence missionnaire et les politiques coloniales. Cette survivance est tributaire de savoirs, de valeurs et de coutumes transmis de génération en génération. Cet article explore l'art de la communauté wendat et ses éléments constitutifs : la fabrication d'objets, la tradition orale, l'engagement actif des membres de la collectivité dans les pratiques traditionnelles, ainsi que l'adaptation des pratiques ancestrales aux préoccupations actuelles. Il montre comment la production artistique wendat, dans sa force expressive, contribue à la continuité et cohésion sociale de la nation wendat.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Land and Beaded Identity: Shaping Art Histories of Indigenous Women of the Flatland - Robertson, Carmen (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Le territoire constitue une force déterminante dans la création artistique. Les prairies austères, notamment, exigent des artistes actuels comme de ceux qui les ont précédés une adaptation constante, déterminée par l'accès aux ressources et la nécessité de mobilité. Cet article s'intéresse à l'impact du territoire sur la pratique du perlage telle qu'exercée par les femmes autochtones. Il met en relation des exemples de perlage traditionnel conservés dans les collections muséales de la Saskatchewan avec les œuvres de trois artistes contemporaines autochtones des plaines, soit Ruth Cuthand, Judy Anderson et Katherine Boyer. La comparaison vise à mieux comprendre le processus intergénérationnel de transmission des pratiques ancestrales et ainsi révéler comment s'exprime le territoire dans les objets et œuvres ornés de perles, qui contribuent à façonner le récit des plaines.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Decolonial Pedagogy: Examining Sites of Resistance, Resurgence, and Renewal - Wane, Njoki Nathani; Todd, Kimberly L (Palgrave Macmillan, 2018)
"Through innovative and critical research, this anthology inquires and challenges issues of race and positionality, empirical sciences, colonial education models, and indigenous knowledges. Chapter authors from diverse backgrounds present empirical explorations that examine how decolonial work and Indigenous knowledges disrupt, problematize, challenge, and transform ongoing colonial oppression and colonial paradigm. This book utilizes provocative and critical research that takes up issues of race, the shortfalls of empirical sciences, colonial education models, and the need for a resurgence in Indigenous knowledges to usher in a new public sphere. This book is a testament of hope that places decolonization at the heart of our human community." -- Prové de l'editor.
Keywords: 1-Histoire de l'art; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unpacking Culture: Art and Commodity in Colonial and Postcolonial Worlds - Phillips, Ruth B.; Steiner, Christopher Burghard (University of California Press, 1999)
Tourist art production is a global phenomenon and is increasingly recognized as an important and authentic expression of indigenous visual traditions. These thoughtful, engaging essays provide a comparative perspective on the history, character, and impact of tourist art in colonized societies in three areas of the world: Africa, Oceania, and North America. Ranging broadly historically and geographically, Unpacking Culture is the first collection to bring together substantial case studies on this topic from around the world.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Figurative Repatriation First Nations ‘Artist-Warriors’ Recover, Reclaim, and Return Cultural Property through Self-Definition - Kramer, Jennifer (Journal of Material Culture, 2004)
This article begins with an analysis of the problems of ‘physical repatriation’, as I review the case of the return of a First Nations mask to its community of origin. First Nations struggle to fit their concepts of ownership into western ones, where objects are viewed as alienable. As an alternative, the art of John Powell and Marianne Nicolson depicts a ‘figurative repatriation’ that does not rely on either the courts or museums to recognize legal or moral ownership. I argue that these contemporary artworks are social agents, which bring First Nations cultural objects home by staking out territory within museums. These ‘artist warriors’ forcibly recover (both literally and metaphorically) First Nations objects on display in foreign settings and reinscribe meaning at the level of the personal and the communal. They make objectified assertions of native identity that reclaim the right to self-definition. Moreover, these claims are made all the more powerful through their conscious location within an oppositional discourse framed by the Canadian western art world.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

Native Art of the Northwest Coast: A History of Changing Ideas - Townsend-Gault, Charlotte; Kramer, Jennifer (UBC Press, 2013)
This remarkable volume, many years in the making, records and scrutinizes definitions of Northwest Coast Native art and its boundaries. A work of critical historiography, it makes accessible for the first time in one place a broad selection of more than 250 years of writing on Northwest Coast "art." Organized thematically, its excerpted texts are from both published and unpublished sources, some not previously available in English. They cover such complex topics as the clash between oral and written knowledge, transcultural entanglement, the influence of surrealist thinking, and the long history of the deployment of Northwest Coast Native art for nationalist purposes. The selections are preceded by thought-provoking introductions that give historical context to the diverse intellectual traditions that have influenced, stimulated, and opposed each othe
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettling Native Art Histories on the Northwest Coast - Bunn-Marcuse, Kathryn B.; Jonaitis, Aldona (Native art of the Pacific Northwest : a Bill Holm Center series, 2020)
"This edited collection focuses on "unsettling" Northwest Coast art studies, bringing forward voices that uphold Indigenous priorities, engage with past and ongoing effects of settler colonialism, and advocate for practices for more accountable scholarship. Featuring authors with a variety of perspectives, backgrounds, and methodologies, Unsettling Art Histories offers new insights for the field of Northwest Coast art studies. Key themes include discussions of cultural heritage protections and long-standing defenses of natural resources and territory; re-centering women and the critical role they play in transmitting cultural knowledge across generations through materials, techniques, and creations; reflecting on the decolonization work being undertaken in museums; and examining how artworks function beyond previous scholarly framings as living documents carrying information critical to today's inquiries. Re-examining previous scholarship and questioning current institutional practices by prioritizing information gathered in Native communities, the essays in this volume exemplify various methods of "unsettling" and demonstrate how new methods of research have reshaped scholarship and museum practices."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Killing the Indian Maiden: Images of Native American Women in Film - Marubbio, M. Elise (UPSO - University Press of Kentucky E-Books, 2006)
Killing the Indian Maiden examines the fascinating and often disturbing portrayal of Native American women in film. M. Elise Marubbio examines the sacrificial role in which a young Native woman allies herself with a white male hero and dies as a result of that choice. In studying thirty-four Hollywood films from the silent period to the present, she draws upon theories of colonization, gender, race, and film studies to ground her analysis in broader historical and sociopolitical context and to help answer the question, "What does it mean to be an American?"
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

Native Americans on Film: Conversations, Teaching, and Theory - Marubbio, M. Elise; Buffalohead, Eric L. (The University Press of Kentucky, 2012)
The film industry and mainstream popular culture are notorious for promoting stereotypical images of Native Americans: the noble and ignoble savage, the pronoun-challenged sidekick, the ruthless warrior, the female drudge, the princess, the sexualized maiden, the drunk, and others. Over the years, Indigenous filmmakers have both challenged these representations and moved past them, offering their own distinct forms of cinematic expression. Native Americans on Film draws inspiration from the Indigenous film movement, bringing filmmakers into an intertextual conversation with academic
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Femmes et violence de masse. - Myre, Nadia; Uzel, Jean-Philippe (Hors-série, 2018)
"Si tous les groupes humains sont touchés par la violence à grande échelle, les femmes la subissent sous des formes spécifiques, comme en témoignent les assassinats systémiques des femmes et des filles autochtones en Amérique du Nord et en Amérique latine, ou encore les nombreux conflits armés (Syrie, Lybie, Birmanie, entre autres) dans lesquels le viol est érigé en arme de guerre. Les deux phénomènes peuvent d'ailleurs se recouper puisque l'un des tout premiers féminicides à avoir été qualifié et documenté comme tel en Amérique est celui ayant été perpétré contre les femmes mayas durant la guerre civile guatémaltèque au début des années 1980. Cependant, les femmes ne sont pas seulement les victimes de la violence de masse, puisqu'elles sont aussi les premières à témoigner et dénoncer pour faire barrage à cette violence. Ce numéro hors-série regroupe des articles et des projets visuels qui décrivent et analysent la violence de masse liée au genre. Il s'agit de réfléchir sur la manière de représenter cette violence et d'en témoigner, d'autant plus qu'elle est bien souvent rendue invisible et inaudible par le patriarcat, le colonialisme, les intérêts politiques en présence ou l'impéritie de l'État."
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La réponse à la Loi sur les Indiens dans les insoumissions performatives de Lawrence Paul Yuxweluptun, Teharihulen Michel Savard et Louis-Karl Picard-Sioui - Desrochers, Marianne (Université de Montréal, 2017)
Entre l’élaboration de la Loi sur les Indiens du Canada en 1876 et les débuts du mouvement Idle No More en 2012, plus d’un siècle de contestation et d’oppression hétéroclite s’est écoulé pour laisser place à une prise de parole vigoureuse portée par l’ensemble des Premières Nations. C’est dans cette perspective que ce mémoire s’intéresse aux pratiques performatives contemporaines élaborées par Lawrence Paul Yuxweluptun (Salish), Teharihulen Michel Savard (Wendat) et Louis-Karl Picard-Sioui (Wendat), dont les œuvres permettent de dresser un éventail varié des stratégies de résistance se consacrant à la libération du regard colonial. Les performances provocantes de ces trois artistes autochtones mettent en place une esthétique de la violence qui, considérée ici en tant qu’outil efficace de résilience et d’affirmation identitaire, déjoue l’autorité coercitive de la Loi sur les Indiens. Centrée sur une approche interdisciplinaire, cette recherche aborde au préalable l’historicité qui sous-tend la construction symbolique de l’indianité, laquelle fut par la suite démentie par les militant.e.s autochtones à travers une diversité de mouvements sociopolitiques contestataires au cours de la seconde moitié du XIXe siècle. Les œuvres performatives de Yuxweluptun, de Teharihulen et de Picard-Sioui font subséquemment l’objet d’une analyse détaillée en regard d’une réappropriation et d’une subversion des codes de la majorité, ce qui leur permet de défier les pouvoirs politiques, économiques, médiatiques et symboliques d’une société eurocentrique cautionnant encore à ce jour une vision figée de la réalité autochtone. Au-delà de la forme et du contenu, les œuvres performatives des artistes à l’étude réinterprètent les traditions immémoriales des Premières Nations tout en les actualisant, venant ainsi confirmer la persistance d’une spécificité culturelle et réfuter les volontés d’annihilation des puissances étatiques et coloniales.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

La réappropriation comme acte politique à l'ère de la décolonisation: l'oeuvre de Nadia Myre - Darsigny-Trépanier, Maude (Université du Québec à Montréal, 2019)
Ce mémoire cherche à dresser l'historiographie de l'artiste anishnabé Nadia Myre. Il s'agit d'une analyse à la fois qualitative et quantitative de près de 200 textes récoltés au sujet de l'artiste du début de sa carrière (1995) jusqu'en 2016. En plus d'offrir une visualisation de l'accomplissement de celle-ci avec la création d'une feuille de calcul, le présent mémoire cherche aussi à analyser les différents propos des auteur.es au sujet de la pratique d'une artiste autochtone en territoire appelé Canada. Les œuvres les plus marquantes de l'artiste sont également analysées en profondeur.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Ossements animaux dans l’art autochtone actuel Discours sur la mort, la résurgence et la guérison - Marcoux, Gabrielle (Recherches amérindiennes au Québec, 2015)
Les ossements animaux occupent des fonctions pratiques et rituelles extrêmement variées et complexes au sein des cultures ancestrales atikamekw et innue, que ce soit sur le plan spirituel, alimentaire, artistique ou autre. Encore aujourd’hui, en plus d’évoquer le trépas, les ossements font référence aux pratiques de communication avec les esprits animaux - comme la scapulomancie - et à la vision holistique du monde chez les peuples algonquiens. En intégrant des peaux et des fragments de squelettes animaux à leurs oeuvres portant sur des réalités contemporaines de pertes et de négociations intimes et collectives d’ordre culturel et territorial, les artistes Sonia Robertson et Eruoma Awashish parviennent à réactualiser le pouvoir de guérison et de résurgence traditionnellement associé aux ossements. Ainsi, la mise en scène d’os permet à ces créatrices de réécrire l’histoire de lieux chargés de sens et de réaffirmer l’importance actuelle de notions spirituelles, identitaires et culturelles autochtones ancestrales dans un contexte de réaffirmation collective et individuelle
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Futurisms: Transcending Past/Present/Future - Herr, Chelsea; Well-Off-Man, Manuela; Fricke, Suzanne Newman (IAIA Museum of Contemporary Indian Arts, 2020)
Indigenous Futurisms: Transcending Past/Present/Future investigates a major trend in Contemporary Native Art--the rise of futuristic or science-fiction inspired Native American art. The essays and artworks present the future from a Native perspective and illustrate the use of Indigenous cosmology and science as part of tribal oral history and ways of life. Several of the artists use sci-fi related themes to emphasize the importance of Futurism in Native cultures, to pass on tribal oral history and to revive their Native language. However, Indigenous Futurism also offer a way to heal from the traumas of the past and present--the post-apocalyptic narratives depicted in some of the artworks are often reality for Indigenous communities worldwide.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Aesthetics, Violence, and Indigeneity. - Rickard, Jolene (Public, 2016)
This essay considers the intersectionality between the field of art history focused on the subject category of Native American or Indigenous art and Indigenous Studies. Methodological gaps in the field of art history are discussed through the canonical genre of landscape art with a comparative reference to key exhibitions; Land Spirit Power: First Nations at the National Gallery of Canada, (1992), The West As America: Reinterpreting Images of the Frontier, 1820-1920, (1991), Submuloc Show/Columbus Wohs (1992), Our Land/Ourselves: Contemporary Native American Landscape (1991) and Picturing the Americas: Landscape Painting from Tierra del Fuego to the Artic (2015). The aestheticization of the colonization of the Americas as represented in the genre of landscape art is interrogated as a form of historical violence that needs to be decolonized within the field of art history.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Partial Recall - Benally, Suzanne (New Press, 1992)
In Partial Recall, twelve Native American artists and writers look deep into the images that have shaped our ideas of "Indianness," and explore the complex relationship of photography to identity. For this volume, edited and introduced by Lucy Lippard, each contributor has chosen one or two photographs as the point of departure for their original poetic, historical, political, or autobiographical essays. With an additional portfolio of more than sixty photographs drawn from around the country, Partial Recall is a unique and valuable anthology.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Absorbing or Obscuring the Absence of a Critical Space in the Americas for Indigeneity: The Smithsonian's National Museum of the American Indian - Rickard, Jolene (Res: Anthropology and Aesthetics, 2007)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; _Nettoyé

Visualizing Sovereignty in the Time of Biometric Sensors - Rickard, Jolene (South Atlantic Quarterly, 2011)
Multiple expressions of sovereignty beyond a narrow legal interpretation are discussed through the artwork of contemporary Iroquois artists, G. Peter Jemison (Seneca), Alan Michelson (Mohawk), Samuel Thomas (Cayuga), and Marie Watt (Seneca). Michelson's installation at the Massena homeland security border checkpoint between the United States, Canada, and the Mohawk Nation, titled The Third Bank of the River, draws on the Guswentah or Two Row Wampum underscoring the problematic yet ongoing assertion of Haudenosaunee sovereignty. A link is made between the work of these artists and the 2008 Courtney Hunt film, Frozen River, based on the cultural and political understanding of the Two Row Wampum. The Guswentah is discussed as a demonstration of sovereignty and is historicized through Cayuga chief Deskaheh's call for the recognition of Haudenosaunee sovereignty at the League of Nations in Geneva, in 1923, John Mohawk's 1978 Basic Call to Consciousness, and more recently, Taiaiake Alfred's 1999 Peace, Power, Righteousness. These artists demonstrate the critical role they play in the ongoing formation of sovereignty as a visual or aesthetic issue in conjunction with its historic legal positioning.
Keywords: 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La muséologie collaborative au Canada : le positionnement du Musée McCord à l’égard des communautés autochtones - Franco, Marie-Charlotte (Musées, mutations…, 2019)
Résumé livre : 4e de couv.: Les mutations qui se sont amorcées à partir de la fin de la Seconde Guerre mondiale et qui connaissent une accélération rapide avec les crises sociales, culturelles, économiques et environnementales contemporaines ont transformé le paysage muséal et les visions dont les musées se soutiennent et qu'ils entretiennent. La plupart des travaux produits au cours de ces années ont été portés par ces transformations et y contribuent : la recherche en muséologie s'est elle-même dissociée de la recherche dans les musées dans les années 1980. De plus, quelque chose s'est noué entre un tournant communicationnel dans les musées et un développement de la réflexion théorique et critique sur la communication. Dans une approche résolument pluridisciplinaire, cet ouvrage se propose d'analyser ces évolutions dans leurs dimensions institutionnelles, culturelles, communicationnelles, historiques, patrimoniales. Les perspectives réunies ici contribueront, sans aucun doute, à mettre au jour les mouvements de fond actuels, les tendances qui travaillent les institutions elles-mêmes, et le poids de ces changements dans la formulation des enjeux théoriques en muséologie.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le musée: un outil de développement identitaire et communautaire en contexte autochtone? : le cas du Musée des Abénakis à Odanak - Franco, Marie-Charlotte (Université du Québec à Montréal, 2012)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Numéro spécial : Cinémas et médias autochtones dans les Amériques : récits, communautés et souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé